Augmented reality in influencing interest in learning mathematics: Systematic literature review - Diah Ayu Setyaningsih; Siti Fatimah As-Salamah; Eka Denti Setiyani; Dina Fakhriyana (Universitas Sarjanawiyata Tamansiswa, 2024)
Learning using technology can grow students' interest, one of which is augmented reality, which can attract students' interest in learning mathematics. This research explores AR forms and responses to students' interest in learning mathematics after using AR. The research method used is a systematic literature review. For this research, a synthesis of relevant studies was created through the PoP (Publish or Perish) application by searching for articles using Google Scholar. Based on the selection results obtained, 740 articles. Ten duplicate articles were found, 143 articles that did not contain any keywords, 561 articles that did not meet the researcher's criteria, and seven articles that did not answer the researcher's question, resulting in 19 basic studies published between 2013 and 2023. The research results provide information that there are forms of AR that can influence interest. Students learn mathematics, namely AR learning media in AR playing cards, 3-dimensional AR, AR text-to-speech applications, AR building space, learning media with magic books, AR and Flash Card applications, and other Android-based AR applications. Augmented Reality (AR) has a very positive impact on students learning mathematics. Thus, educators may consider additional training in the use of AR technology and develop learning strategies that include elements of AR to support the achievement of student mathematical learning objectives effectively.